Selected examples of natural stones from Italy and Germany used in architectural objects in Krakow – a short geological excursion - Górny, Zbigniew (Geotourism/Geoturystyka, 2018)
The aim of the following paper is to propose a trip to selected sites in Kraków where decorative stones imported from Italy and Germany were used. The main types of stones are presented together with their commercial names, quarries, age and decorative values. Additionally, the author identified the regions in Italy and Germany from which stones were supplied. The most popular Italian decorative stones are the Carrara marbles quarried in the vicinity of Carrara and the “Ammonitico rosso” limestones extracted in the neighbourhood of Verona. Interesting are also porphyries from Trident, limestones from Brescia, travertines from Tivoli and granites and travertines quarried in Sardynia. In Germany large deposits of Upper Jurassic limestones are located in northern Bavaria (Franconia).